2012
DOI: 10.1515/hsz-2012-0235
|View full text |Cite
|
Sign up to set email alerts
|

The gateway to chloroplast: re-defining the function of chloroplast receptor proteins

Abstract: : Chloroplast biogenesis often requires a tight orchestration between gene expression (both plastidial and nuclear) and translocation of ~ 3000 nuclear-encoded proteins into the organelle. Protein translocation is achieved via two multimeric import machineries at the outer (TOC) and inner (TIC) envelope of chloroplast, respectively. Three components constitute the core element of the TOC complex: a β -barrel protein translocation channel Toc75 and two receptor constituents, Toc159 and Toc34. A diverse set of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 115 publications
(181 reference statements)
0
12
0
Order By: Relevance
“…This clone, however, lacked a true start methionine, therefore was most likely N-terminally incomplete. In addition, the abundance of the acidic amino acids glutamic acid and aspartic acid as well as the hydroxyl-containing serine and threonine that has been proposed as characteristic features of the A-domain in Arabidopsis Toc159 homologs (Agne et al, 2010; Chang et al, 2012) was also found in both putative A-domain sequences of psToc132 and psToc120. Therefore, both sequences represent genuine A-domains of psToc132 and psToc120 in pea, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…This clone, however, lacked a true start methionine, therefore was most likely N-terminally incomplete. In addition, the abundance of the acidic amino acids glutamic acid and aspartic acid as well as the hydroxyl-containing serine and threonine that has been proposed as characteristic features of the A-domain in Arabidopsis Toc159 homologs (Agne et al, 2010; Chang et al, 2012) was also found in both putative A-domain sequences of psToc132 and psToc120. Therefore, both sequences represent genuine A-domains of psToc132 and psToc120 in pea, respectively.…”
Section: Resultsmentioning
confidence: 91%
“…This simplified view is true for most mitochondrial and chloroplastic proteins. Various aspects of the organellar protein import have been extensively reviewed elsewhere [25][26][27][28][29][30][31][32].…”
Section: Glossarymentioning
confidence: 99%
“…Toc75, Toc34, and Toc159 are integral membrane proteins that form complexes in the outer membrane with a minimal size of 800 kDa and a stoichiometry estimated at 4:4:1 or 3:3:1 (Toc75:Toc34:Toc159) (Schleiff et al, 2003; Kikuchi et al, 2006; Chen and Li, 2007). Toc34 and Toc159 bind to the transit peptides of newly synthesized preproteins at the chloroplast surface via their GTPase domains (G-domains) and initiate translocation across the outer membrane by transferring preproteins to Toc75 through a series of intermolecular events controlled by their intrinsic GTPase activities (Figure 1B) (Kessler and Schnell, 2002; Li et al, 2007; Chang et al, 2012; Lee et al, 2013). Genetic and biochemical data indicate that transit peptide binding at the receptors regulates both homo- and heterodimerization between their cytoplasmic GTPase-domains, which in turn controls nucleotide exchange, hydrolysis and the initiation of preprotein translocation (Bauer et al, 2002; Smith et al, 2002; Jelic et al, 2003; Weibel et al, 2003; Becker et al, 2004; Yeh et al, 2007; Koenig et al, 2008a,b; Lee et al, 2009; Rahim et al, 2009; Oreb et al, 2011).…”
Section: Overview Of Toc Functionmentioning
confidence: 99%
“…A multimeric complex in the plastid outer envelope membrane, referred to as TOC (translocon at the outer membrane of chloroplasts), recognizes the majority of plastid-destined proteins at the organelle surface (Kessler and Schnell, 2009; Chang et al, 2012). TOC components bind the N-terminal transit peptides of newly synthesized preproteins and function in coordination with a second complex at the inner envelope membrane, referred to as TIC (translocon at the inner membrane of chloroplasts), to provide direct transport of preproteins from the cytoplasm to the stroma (Li and Chiu, 2010; Jarvis and Lopez-Juez, 2013).…”
Section: Introductionmentioning
confidence: 99%